Promotion of mangrove-friendly shrimp aquaculture in Southeast Asia - Sulit, V.T; Ebron, N.R; Tendencia, I.T; Gotera, S.C (SEAFDEC Aquaculture Department, 2004)
This publication comprises two major parts : Report on the Regional Seminar-Workshop on Mangrove-Friendly Shrimp Aquaculture, Bangkok, Thailand, 24-27 June 2003 ; Report on the Mangrove Friendly Shrimp Culture Project: Phase I (2000-2003)